2020
DOI: 10.1186/s12903-020-01339-5
|View full text |Cite
|
Sign up to set email alerts
|

Classification and morphology of middle mesial canals of mandibular first molars in a southern Chinese subpopulation: a cone-beam computed tomographic study

Abstract: Background Cone-beam computed tomography (CBCT) was employed to study the morphology and curvature of middle mesial canals (MMCs) of mandibular first molars (MFMs). Methods CBCT scanning was performed on MFMs of 1100 patients. Patients' images that met the inclusion criteria were divided into group A (< 40 years old) and group B (≥ 40 years old) for further study. The images were used to study the incidence of MMCs at different ages, measure the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…CBCT may be considered if the clinician suspects the presence of multiple root canals. The accuracy of CBCT is much higher than that of periapical radiographs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBCT may be considered if the clinician suspects the presence of multiple root canals. The accuracy of CBCT is much higher than that of periapical radiographs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, no meta-analysis was performed on age and its relation with the prevalence of MMC because of the insufficient data and heterogeneity of the most included studies regarding age. However, some studies reported that the prevalence of identifiable MMC decreases as age increases [ 8 , 46 ]. Therefore, the prevalence of identifiable MMC could be related to secondary dentin deposition [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A importância da TCFC na endodontia, especialmente para a localização e estabelecimento da anatomia do canal MM em primeiros molares inferiores, está demonstrada nos resultados apresentados. Isso também está demonstrado em inúmeros estudos revisados (La et al, 2010;de Toubes et al, 2012;Chavda & Garg, 2016;Versiani et al, 2016;Tahmasbi et al, 2017;Srivastava et al, 2018;Tomaszewska et al, 2018;Honap et al, 2020;Kuzekanani et al, 2020;Weinberg et al, 2020;Xu et al, 2020;Yang et al, 2020) que utilizaram a TCFC como critério de avaliação isoladamente, ou em comparação com outros métodos.…”
Section: Discussionunclassified
“…Em relação ao gênero, nesse estudo, não houve diferença estatisticamente significante na incidência entre mulheres e homens o que também foi constatado em outros estudos (Huang et al, 2010;Nosrat et al, 2015;Tahmasbi et al, 2017;Srivastava et al, 2018;Xu et al, 2020;Yang et al, 2020). (Nosrat et al, 2015;Chavda et al, 2016, Versiani et al, 2016Tahmasbi et al, 2017;Srivastava et al, 2018;Weinberg et al, 2020;Xu et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation